Implementation of Total Communication in Islamic Religion Learning in Deaf Children in Spirit Dakwah Indonesia Foundation - Ferra Puspito Sari; Mochammad Sinung Restendy (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2020)
Disability is a separate difficulty in the learning process, especially in religious learning. Being very complete when a deaf child accepts religious learning both theory and practice, so that the right way of communicating is needed by the teacher in dealing with deaf children. Not only that, there are still many regions that lack awareness of religious education for children with disabilities especially those who are deaf. Deaf children are actually still capable and deserving of religious learning, because they can still use the rest of the hearing (aural), use gestures and finger spelling (manual) that are visualized, and read utterances and speech (oral) that sound even though sometimes unclear, where these three things are communication media. This is where deaf children can learn by using a total communication system which involves receptive components (reading writing, utterances, gestures, finger and gesture / mimic spelling) and expressive components (speaking, gesturing, finger spelling, writing and gesture / expression) both are interactive. Observations were carried out at the Indonesian Spirit Da'wah Foundation by applying total communication to its students in Qurani Informal Education (TPQLB) Indonesian Spirit Dakwah Foundation as a communication system in religious learning both theory and practice. From the evaluation results, it was concluded that the application of total communication had a positive influence on learning Islamic religion in deaf children at the Spirit Dakwah Indonesia Foundation, children who were deaf in focus and interested in learning, they could re-explain the material taught simply either orally and sign language.